Know Your Doctor: Topic Modeling and Sentiment Analysis Based Approach To Review Doctor - Kavya, K; Sreejith, C (International Journal of Computer Sciences and Engineering, 2018)
Nowadays people tend to search for doctors or firms through business review websites. They naturally opt for doctors that have the very best ratings and an outsized variety of reviews that support those high ratings. Hundreds or perhaps thousands of reviews will be given to the best-rated ones beneath their profiles, and comparing a high rated option to every alternative becomes a tedious task. This paper aims to address this issue by making a summarizer to analyze the doctors review by performing topic modeling using Latent Dirichlet Allocation(LDA) and Word2Vec based sentiment analysis. LDA is a standard Natural Language Processing (NLP) technique to determine topics from a large corpus. Word2vec based sentiment analysis is used to study people's opinions, attitudes and emotions towards a review. Word2vec is a neural network with twolayer that embeds the text corpus to a set of feature vectors of the words in the corpus. The reviews are taken from Yelp, an online rating website, of doctors across San Francisco. As a result of this study, a snapshot is created for each doctor with most dominant topics and the overall sentiment from their reviews.